Total quality management : a cross functional perspective (New York : John Wiley & Sons, 1996)
The emphasis of Quality is pervading every facet of business, and managers are required to know and apply TQM principles. This book explores the strategic role of quality global competition, the roles of management in attaining quality excellence, the structures and systems needed to support a total quality strategy, and the main statistical and analytical tools for achieving quality improvement and control.
Includes index.
Keywords: Total quality management